Ebola virus requires a host scramblase for externalization of phosphatidylserine on the surface of viral particles - Nanbo, Asuka; Maruyama, Junki; Imai, Masaki; Ujie, Michiko; Fujioka, Yoichiro; Nishide, Shinya; Takada, Ayato; Ohba, Yusuke; Kawaoka, Yoshihiro (PLoS pathogens, 2018)
Cell surface receptors for phosphatidylserine contribute to the entry of Ebola virus (EBOV) particles, indicating that the presence of phosphatidylserine in the envelope of EBOV is important for the internalization of EBOV particles. Phosphatidylserine is typically distributed in the inner layer of the plasma membrane in normal cells. Progeny virions bud from the plasma membrane of infected cells, suggesting that phosphatidylserine is likely flipped to the outer leaflet of the plasma membrane in infected cells for EBOV virions to acquire it. Currently, the intracellular dynamics of phosphatidylserine during EBOV infection are poorly understood. Here, we explored the role of XK-related protein (Xkr) 8, which is a scramblase responsible for exposure of phosphatidylserine in the plasma membrane of apoptotic cells, to understand its significance in phosphatidylserine-dependent entry of EBOV. We found that Xkr8 and transiently expressed EBOV glycoprotein GP often co-localized in intracellular vesicles and the plasma membrane. We also found that co-expression of GP and viral major matrix protein VP40 promoted incorporation of Xkr8 into ebolavirus-like particles (VLPs) and exposure of phosphatidylserine on their surface, although only a limited amount of phosphatidylserine was exposed on the surface of the cells expressing GP and/or VP40. Downregulating Xkr8 or blocking caspase-mediated Xkr8 activation did not affect VLP production, but they reduced the amount of phosphatidylserine on the VLPs and their uptake in recipient cells. Taken together, our findings indicate that Xkr8 is trafficked to budding sites via GP-containing vesicles, is incorporated into VLPs, and then promote the entry of the released EBOV to cells in a phosphatidylserine-dependent manner.